Steam and KOH Activated Carbons from Peach Stones - Duranoglu, D.; Beker, U. (TAYLOR & FRANCIS INC, 2012)
Peach-stone-based activated carbons were prepared by using steam and KOH activation at 800 degrees C. The effects of solid/liquid phase KOH and steam activation, alkali and acidic pre-treatment, and also single-step activation on activated carbon properties were investigated comprehensively. The activated carbon produced by solid phase KOH impregnation showed the highest surface area of 835 m(2)/g and micropore volume of 0.412 cm(3)/g. Besides, single-step steam activation produced a highly microporous carbon having a relatively high surface area of 608 m(2)/g and micropore volume of 0.331 cm(3)/g. Peach-stone-based activated carbons with well-developed pore structure and functional properties were achieved, comparable to the commercial carbon, CPG-LF (Chemviron Carbon). The produced carbons were tested for Chromium (VI) removal from aqueous solution. Some of the activated carbons showed higher Chromium (VI) adsorption capacity than commercial activated carbon, CPG-LF (Chemviron Carbon).
Keywords: activated carbon; chromium; KOH; peach stone; steam; SURFACE-AREA; ADSORPTION; POROSITY; Energy & Fuels; Engineering; Environmental Sciences & Ecology